Retinal degenerative diseases: role of dietary supplements in retinal health - D. Mohan Kumar; Priti Talwar (Discover Food)
Abstract Retinal degeneration is a progressive condition that affects the retina, the light-sensitive layer, and deteriorates the inner retinal cells that encompass retinal pigment epithelium, photoreceptors, and ganglion cells that are essential for eyesight. Multiple factors including aging, genetic factors, oxidative stress, inflammation, and environmental factors can contribute to retinal degeneration. Retinal degeneration is seen predominantly in Age-related Macular degeneration, Diabetic retinopathy, Glaucoma, and Retinitis pigmentosa that contribute to the leading cause of vision loss. The search for potential and effective therapeutic interventions in the management of retinal degeneration has led to increased interest in dietary supplements, particularly those rich in antioxidant properties. Dietary supplements have been proposed as an ideal source for preventing retinal degeneration, especially supplements containing significant levels of antioxidants that help to reduce the damage to retinal cells. Notably, dietary interventions with carotenoids, flavonoids, alkaloids, amino acids, fatty acids, vitamins, and minerals have shown positive effects in both preclinical and clinical studies by preserving the retinal structure, revitalizing retinal health, delaying disease progression, and improving visual function. To explore this topic further, a systematic search strategy was employed in recent studies that are focused on cell lines, animal models, and human subjects. Ultimately, this review highlights the potential of dietary supplements that should be used as adjunctive therapies alongside comprehensive medical management, aiming to maximize their potential benefits in treating and preventing retinal degeneration.